2011
DOI: 10.1007/s10847-011-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism of binding of chromate to cucurbit[6]uril: a DFT study

Abstract: We report the binding of chromate, a toxic heavy metal ion to the macrocyclic host molecule, cucurbituril using density functional theory. Due to the anionic nature of the guest molecule and the portals of the host molecule, we propose that the binding mechanism should be assisted by cations. The calculated barrier for chromate binding to cucurbituril is found to be *17 kcal mol -1 . The large barrier can be attributed to portal opening of the host molecule, electrostatic repulsion between the guest molecule a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…were found to make stable complexes with CB[6]. Further, Ghosh and co-workers , studied complexation of CB[6] with halide ion and solvated chromate ion. The current study becomes more relevant as cucurbiturils have already been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…were found to make stable complexes with CB[6]. Further, Ghosh and co-workers , studied complexation of CB[6] with halide ion and solvated chromate ion. The current study becomes more relevant as cucurbiturils have already been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical methodology has recently become an important tool in the study of supramolecular host–guest complexes. The various components of the methodology have gradually improved, and more accurate results are possible today. Advances in density functional theory are, of course, of great importance here, but also important is the development of various corrections, such as dispersion and free energy corrections. , …”
Section: Introductionmentioning
confidence: 99%
“…Studies involving complexation of CB [6] with halide ion and solvated chromate ion were investigated by Ghosh and co-workers. 62,63 In view of the potential use of CB [6] as a host to different gases, the present study attempts to determine relative stability of different gases encapsulated by CB [6]. In this way, the selectivity in gas adsorption by CB [6] over a large spectrum of gas molecules can be predicted.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In fact, Kim et al showed that CB[6] adsorbs CO 2 selectively over CO and CH 4 in the solid state. Studies involving complexation of CB[6] with halide ion and solvated chromate ion were investigated by Ghosh and co-workers. , …”
Section: Introductionmentioning
confidence: 99%